2023
DOI: 10.1038/s41538-023-00190-6
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, but not high-fat diet, is associated with bone loss that is reversed via CD4+CD25+Foxp3+ Tregs-mediated gut microbiome of non-obese mice

Abstract: Osteoporosis is characterized by decreased bone mass, microarchitectural deterioration, and increased bone fragility. High-fat diet (HFD)-induced obesity also results in bone loss, which is associated with an imbalanced gut microbiome. However, whether HFD-induced obesity or HFD itself promotes osteoclastogenesis and consequent bone loss remains unclear. In this study, we developed HFD-induced obesity (HIO) and non-obesity (NO) mouse models to evaluate the effect of HFD on bone loss. NO mice were defined as bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 90 publications
0
4
0
Order By: Relevance
“…There are also reports that this type of diet affects the structure and health of the skeletal system, although opinions on the direction of this effect are clearly divided [25,26]. On the one hand, it has been suggested that excess adipose tissue deposited during intake of a high-fat diet, by increasing mechanical load, may stimulate bone-formation processes, leading to the achievement of peak bone mass and reducing the risk of osteoporosis [2,3].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There are also reports that this type of diet affects the structure and health of the skeletal system, although opinions on the direction of this effect are clearly divided [25,26]. On the one hand, it has been suggested that excess adipose tissue deposited during intake of a high-fat diet, by increasing mechanical load, may stimulate bone-formation processes, leading to the achievement of peak bone mass and reducing the risk of osteoporosis [2,3].…”
Section: Discussionmentioning
confidence: 99%
“…The literature indicates that obesity, including obesity induced by chronic intake of a high-fat diet, may be accompanied by the development of numerous disorders, such as metabolic syndrome, insulin resistance, diabetes, cardiovascular disease, and even cancers [ 23 25 ]. There are also reports that this type of diet affects the structure and health of the skeletal system, although opinions on the direction of this effect are clearly divided [ 25 , 26 ]. On the one hand, it has been suggested that excess adipose tissue deposited during intake of a high-fat diet, by increasing mechanical load, may stimulate bone-formation processes, leading to the achievement of peak bone mass and reducing the risk of osteoporosis [ 2 , 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations